Vesper flights : new and collected essays - Macdonald, Helen, 1970- (Grove Press, 2020)
Presents a collection of essays about humanity's relationship with nature, exploring subjects ranging from captivity and immigration to ostrich farming and the migrations of songbirds from the Empire State Building.